2002
DOI: 10.1016/s0042-6989(02)00197-9
|View full text |Cite
|
Sign up to set email alerts
|

The extent of crowding in peripheral vision does not scale with target size

Abstract: Identifying a target is more difficult when distracters are present within a zone of interaction around the target. We investigated whether the spatial extent of the zone of interaction scales with the size of the target. Our target was a letter T in one-of-four orientations. Our distracters were four squared-thetas in one-of-two orientations, presented one in each of the four cardinal directions, equidistant from the target. Target-distracter separation was varied and the proportion of correct responses at ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
158
4
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 49 publications
15
158
4
1
Order By: Relevance
“…The stimuli in Bouma's (1970) study were not scaled for eccentricity, whereas the stimuli used here were. This may account for our different results, since Strasburger et al (1991) have found that both the size of the flank and its distance from the target affect crowding (although see Tripathy & Cavanagh, 2002, for data that suggest otherwise).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The stimuli in Bouma's (1970) study were not scaled for eccentricity, whereas the stimuli used here were. This may account for our different results, since Strasburger et al (1991) have found that both the size of the flank and its distance from the target affect crowding (although see Tripathy & Cavanagh, 2002, for data that suggest otherwise).…”
Section: Discussionmentioning
confidence: 73%
“…Although SD threshold is an unusual method for determining visual crowding, it may be better than the typical method of measuring percentage correct for a fixed SD. In a recent study in which SD was varied, Tripathy and Cavanagh (2002) found different degrees of crowding, depending on SD. In their study, the change in SD was used to equate performances for individual targets.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…13,22 One explanation is that crowding is a result of the limitation of the spatial resolution of attention. 23,24 In this model, stimulus features are taken into account and crowding occurs only when flankers share the defining dimension of the target (e.g., color or spatial frequency). Thus, when two or more items are within the smallest possible selected region of attention and share a defining feature, the individual item is not identified.…”
mentioning
confidence: 99%
“…Thus, Pelli, Palomares, and Majaj (2004) argued that crowding limits all vision and has nothing to do with attention, whereas Strasburger (2005) argued that the impairment of character recognition by crowding is caused, to a large extent, by spatially imprecise focusing of attention (see also He, Cavanagh, & Intriligator, 1996;Intriligator & Cavanagh, 2001;Tripathy & Cavanagh, 2002). For example, in the flanker paradigm used by Bouma (1970) and Strasburger, among others, the observer must discriminate the target (center character) from the distractors (flanker characters).…”
mentioning
confidence: 99%